Antecedents for crafting a sense of coherence among healthcare employees - Jaldestad, Ellen; Dellve, Lotta (Frontiers in Psychology, 2025)
Job crafting–an active form of job redesign–has been widely studied within healthcare in recent years, possibly because of its many positive outcomes in this context. Job crafting can be described as actions to redesign a current work situation to increase the fit of a person’s abilities, resources, and desires. Among the positive consequences of job crafting are employee well-being, work engagement, and a productive workforce. The Swedish healthcare sector struggles with challenging work environments and staff shortages, and health-promoting activities can thus be particularly important for employees’ wellbeing. To identify antecedents of job crafting that can promote well-being within public healthcare, semi-structured interviews were conducted with employees and managers in five different healthcare departments. Departments with daytime activities only and 24/7 operations were represented in the study. On an individual level, being a driven person as well as focusing on the patient were found to precede health-promoting job crafting. Being a driven person indicates an ability to deal with restrictive work conditions, such as a lack of support among colleagues and managers, for those who choose to craft their jobs. Working autonomously or in cross-professional teams were contextual antecedents that led to a more comprehensible work situation and different degrees of perceived freedom in work. Utilizing these degrees of freedom through job crafting strategies with the patient’s best interests in mind led to a work situation that was considered more manageable and meaningful. When planning how to facilitate health-promoting job crafting among healthcare employees, it is recommended to keep in mind that job crafting antecedents seem to interplay on different organizational and individual levels.